2013
DOI: 10.1007/s00441-013-1763-y
|View full text |Cite
|
Sign up to set email alerts
|

Homologous and heterologous desensitization of guanylyl cyclase-B signaling in GH3 somatolactotropes

Abstract: The guanylyl cyclases, GC-A and GC-B, are selective receptors for atrial and C-type natriuretic peptides (ANP and CNP, respectively). In the anterior pituitary, CNP and GC-B are major regulators of cGMP production in gonadotropes and yet mouse models of disrupted CNP and GC-B indicate a potential role in growth hormone secretion. In the current study, we investigate the molecular and pharmacological properties of the CNP/GC-B system in somatotrope lineage cells. Primary rat pituitary and GH3 somatolactotropes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…However, RT-PCR analysis revealed that GH3 cells failed to express transcripts for Npr3 encoding NPR-C (Fig. 1 d), in keeping with our previous studies (Thompson et al 2014 ). As the inhibition of cAMP production has previously been indicated as evidence of NPR-C activity (Sciarretta et al 2013 ), we examined the potential effect of CNP on forskolin (FSK)-stimulated cAMP accumulation in GH3 cells.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, RT-PCR analysis revealed that GH3 cells failed to express transcripts for Npr3 encoding NPR-C (Fig. 1 d), in keeping with our previous studies (Thompson et al 2014 ). As the inhibition of cAMP production has previously been indicated as evidence of NPR-C activity (Sciarretta et al 2013 ), we examined the potential effect of CNP on forskolin (FSK)-stimulated cAMP accumulation in GH3 cells.…”
Section: Resultssupporting
confidence: 91%
“…As shown (Fig. 1 b, c), both CNP and ANP caused an increase in the total concentration of cGMP, indicating the presence of functional GC-B and GC-A receptors, as we and others have described previously (Shimekake et al 1994 ; Fowkes et al 2000 ; Thompson et al 2014 ). To establish whether CNP and ANP could stimulate P-ERK1/2, we stimulated GH3 cells with the same concentration range of both peptides for 15 min, prior to the extraction of total protein and Western blotting for phosphorylated ERK1/2 (P-ERK1/2).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Signaling through various other hormones and growth factors also reduces the guanylyl cyclase activity of NPR2 in other cells, for example, vasopressin (Abbey and Potter, 2002), PDGF (Chrisman and Garbers, 1999;Abbey and Potter, 2003), lysophosphatidic acid (Abbey and Potter, 2003;Potthast et al, 2004), sphingosine-1-phosphate (Abbey-Hosch et al, 2005) and thyrotropin-releasing hormone (Thompson et al, 2014). In studies of sphingosine-1-phosphate acting on cultured fibroblasts that overexpress NPR2 (Abbey-Hosch et al, 2005), there is a correlation between dephosphorylation and the decrease in guanylyl cyclase activity.…”
Section: Discussionmentioning
confidence: 99%